Perspektif Maqashid As-Maqasid As-Shari’ah Dalam Sertifikasi Halal Di Indonesia: Analisis Terhadap Proses Dan Implementasi - Parmujianto, Parmujianto (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study aims to analyze the halal certification process in Indonesia from the perspective of maqasid as-shari'ah. This study uses literature study and interview methods to examine the suitability of the halal certification process by applying the principles of maqasid as-shari'ah. The results of the study show that the halal certification process in Indonesia has fulfilled several principles of maqasid as-shari'ah, such as maintaining product purity and safety. However, this study found several challenges in the implementation of halal certification, such as lack of public awareness and lack of resources. This study also recommends that the halal certification process in Indonesia can be improved by considering the principles of Maqasid as-Shari'ah more comprehensively.